Evolutionary Dynamics of the Ty3/Gypsy LTR Retrotransposons in the Genome of Anopheles gambiae - Tubio, Jose Manuel C. (Public Library of Science, 2011)

(untitled)
Ty3/gypsy elements represent one of the most abundant and diverse LTR-retrotransposon (LTRr) groups in the Anopheles gambiae genome, but their evolutionary dynamics have not been explored in detail. Here, we conduct an in silico analysis of the distribution and abundance of the full complement of 1045 copies in the updated AgamP3 assembly. Chromosomal distribution of Ty3/gypsy elements is inversely related to arm length, with densities being greatest on the X, and greater on the short versus long arms of both autosomes. Taking into account the different heterochromatic and euchromatic compartments of the genome, our data suggest that the relative abundance of Ty3/gypsy LTRrs along each chromosome arm is determined mainly by the different proportions of heterochromatin, particularly pericentric heterochromatin, relative to total arm length. Additionally, the breakpoint regions of chromosomal inversion 2La appears to be a haven for LTRrs. These elements are underrepresented more than 7-fold in euchromatin, where 33% of the Ty3/gypsy copies are associated with genes. The euchromatin on chromosome 3R shows a faster turnover rate of Ty3/gypsy elements, characterized by a deficit of proviral sequences and the lowest average sequence divergence of any autosomal region analyzed in this study. This probably reflects a principal role of purifying selection against insertion for the preservation of longer conserved syntenyc blocks with adaptive importance located in 3R. Although some Ty3/gypsy LTRrs show evidence of recent activity, an important fraction are inactive remnants of relatively ancient insertions apparently subject to genetic drift. Consistent with these computational predictions, an analysis of the occupancy rate of putatively older insertions in natural populations suggested that the degenerate copies have been fixed across the species range in this mosquito, and also are shared with the sibling species Anopheles arabiensis.